Maize bran as an agro-industrial by-product: its bioactive compounds and their potential health benefits - Muzzamal Hussain; Muhammad Ahtisham Raza; Farhan Saeed; Muhammad Afzaal; Tabussam Tufail; Awais Ahmad; Aftab Ahmad; Entessar Al Jbawi (Cogent Food & Agriculture)
The establishment of innovative and sustainable ways to utilize the food moieties is the major concern of the society in modern world. However, there are variety of food components which are being neglected despite of the fact that they are the excellent source of nutritional and bioactive components. Maize (Zea mays L.) is the leading cereal crop in the world, with the highest productivity for feed, food, and industrial uses. It is a milling by-product produced from the outer layer of the maize kernel and an economical and sustainable source of dietary fiber and phenolic compounds. Maize bran is a rich source of bioactive compounds, including non-starch polysaccharides (arabinoxylans and feruloylated arabinoxylans), ferulic, p-coumaric, and syringic acid among other cereal bran. These bioactive compounds have been extracted using different methods and have been reported to reduce the severity of various chronic diseases, like cardiovascular diseases, diabetes mellitus, oxidative damage, and neurodegenerative disorders. In the current review, we focused to conduct an integrative analysis of peer-reviewed research on maize bran; milling, nutritional profile, extraction of bioactive compounds, potential health benefits, and effects on the rheological and sensorial properties of the end product.